Collaborative Care - empowering community in the development of rural primary health workforce and service delivery models - Shannon Nott; Richard Colbran; Mike Edwards (James Cook University, 2023)
Introduction: Across Australia, providing sustainable primary care services in small rural communities (<1000 population) has been increasingly challenging. It is acknowledged that health system planners must take coordinated action to strengthen systems to enable a community-empowered response to such challenges. In partnership with the Australian Government, Collaborative Care is a whole-of-system approach used in five Australian rural sub-regions to align communities, organisations, policy and funding levers with a common purpose in health workforce and service planning (article here).Methods: A synthesis of field observations and experiences of community and jurisdictional partners in planning and implementing a Collaborative Care model.Results: In this presentation, we report on the success factors and challenges in developing models for improved rural primary health care access. Successes include sustained community participation, improved community health workforce literacy, coordination of stakeholders and resources across health and community systems combined with health service planning expertise. Challenges include the time and investment to build a coordinated partnership approach and in identifying mechanisms for ongoing financial sustainability.Discussion: Including community as a partner in design and implementation is a key enabler for achieving a tailored primary health workforce and service delivery model that is acceptable and trusted by communities. The Collaborative Care approach strengthens community through capacity building and integrating existing resources across both primary and acute care services to achieve an innovative and quality rural health workforce model built around the concept of rural generalism. Identifying mechanisms for sustainability will enhance the usefulness of the Collaborative Care Framework.